(untitled) (Biological Sciences - PJSIR, 1998)
Magnesite occurrence in Pakistan appears to be a part of Himalayan Orogenic System as all magnesite deposits occur along the Axial Belt.Two majorgenetic typesof magnesitehavebeenrecognised inPakistan. Crystallin and replacement magnesite hosted in carbonate rocks and cryptocrystalline (amorphous) magnesite hosted in ultramafics. Commercially both types of deposits occurring in KumharandMuslimbagh are importantbut thereserves of Kurnhar arelarge. Magne- site desposits in Pakistan are being mined by open cast method and the production isonly few thousand tons per annum. This paper discusses briefly the quality and size of these magnesite deposits and their possible modern industrial applications.